PROFIL REPRESENTASI MATEMATIS SISWA BERGAYA VERBALIZER DALAM MENYELESAIKAN SOAL PISA - Winda Adelya Rosa; intan bigita kusumawati; soffil widadah (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2021)
In the process of learning mathematics, every individual owns its own way of presenting their mathematical ideas in which those ideas are accumulated from the thinking process that are presented in written form of the model of problem solving and solution. Different way of those mathematical ideas is defined as representation.The aim of this research is to describe the representation skills of student by using cognitive style; verbalizer to answer PISA test. This research used descriptive research design for qualitative research method. This research was done at X MIPA 3 SMA Muhammadiyah 3 Tulangan with academic year 2019/2020. In deciding the subjects, this research employs a questionnaire with cognitive styles; visualizer and verbalizer. The result of the questionnaire showed that there are one student for verbalizer as a research subjects. In analyzing the data, there are three steps, namely data reduction, data display, and conclusion drawing for students' ability in finishing the PISA test. Based on the result of the test and the interview, verbal representation is the representation that used verbalizer cognitive style’ students